Starting age and L1 & L2 interaction - Mihaljević-Djigunović, Jelena (Array, 2010)
The study looks into the multi-competence of early and late beginners by studying the interaction of achievement in their L1 and L2. In the context of this study L1 was Croatian and L2 English. Early beginners are defined as learners who started learning English before age 10 and late beginners as learners who started at 10 or later. The findings of this study show that the multi- competence of early and later beginners differs in terms of interaction of their L1 and L2. It is suggested that early beginners, through their longer exposure to L2, reach the necessary competence levels in their two languages sooner to allow transfer in both directions. Before these levels are reached, L1-L2 interactions are either non-existent or weak.